The role of digital transformation on e-learning at King Khalid University considering the Corona pandemic covid 19 - Abdul Khair, Asia Yaqoub Al Hadi (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to identify the important role that digital transformation plays in activating and developing e-learning, as digital transformation has radically changed in all fields, especially in the field of education, as it allowed the emergence of modern educational methods and methods. With the rapid development in the world of technology and the trend of governments and institutions towards digital in all their services by providing digital services in a smooth and easy way that saves effort, time and money for the beneficiaries, in our current era all institutions have been keen to adopt the concept of digital transformation by replacing traditional digital processes, and developing plans and strategies to ensure the achievement of Its objectives are of quality and efficiency, as the digital transformation is able to create a competitive and attractive technical environment that achieves the highest levels of quality at the lowest costs, and that the spread and use of everything digital has accelerated over the past ten years Several challenges have imposed on traditional education, especially in light of the Corona pandemic (Covid-19), which makes relying on traditional educational methods difficult, so the study came with the aim of identifying the role of digital transformation (digital learning) at King Khalid University on the development and effectiveness of e-learning in light of the pandemic The paper followed the inductive approach and the qualitative approach. Observation, reports, documentary information and King Khalid University websites were used to collect data. The concepts of digital transformation as well as e-learning were addressed, and then a set of results were reached. King Khalid University is distinguished by the existence of an effective electronic system, that the technical environment for information technology has enabled King Khalid University to face the rapid change in the work environment, and the study concluded some recommendations. One of them is that digital transformation is no longer an option, rather it has become a necessity, so it is necessary to keep pace with technological developments and to benefit from them in the transformation towards digital learning.